Bioenergy from biofuel residues and waste. (14th July 2020) - Sheehan, Nathaniel P.; Ng, Andrew; Murray, Kyle; Martinez, Erick; Quell, Kimberly; Ouellette, Charles; Flagg, Timothy; Boyle, John
Abstract: This article is a review of the scientific literature published in 2019 on topics relating to bioenergy from biofuel residues and waste. This literature review is divided into the following sections: Feedstocks, Biodiesel, Bioethanol, Hydrogen, Biohydrogen, Biofuel Residues, Microalgae, and Lignocelluloses.